Degradable Vanadium Disulfide Nanostructures with Unique Optical and Magnetic Functions for Cancer Theranostics. (6th September 2017) - Chen, Yuyan; Cheng, Liang; Dong, Ziliang; Chao, Yu; Lei, Huali; Zhao, He; Wang, Jian; Liu, Zhuang
Abstract: Multifunctional biodegradable inorganic theranostic nano‐agents are of great interest to the field of nanomedicine. Upon lipid modification, VS2 nanosheets could be converted into ultra‐small VS2 nanodots encapsulated inside polyethylene glycol (PEG) modified lipid micelles. Owing to paramagnetism, high near‐infrared (NIR) absorbance, and chelator‐free 99m Tc 4+ labeling of VS2, such VS2 @lipid‐PEG nanoparticles could be used for T1‐weighted magnetic resonance (MR), photoacoustic (PA), and single photon emission computed tomography (SPECT) tri‐modal imaging guided photothermal ablation of tumors. Importantly, along with the gradual degradation of VS2, our VS2 @lipid‐PEG nanoparticles exhibit effective body excretion without appreciable toxicity. The unique advantages of VS2 nanostructures with highly integrated functionalities and biodegradable behaviors mean they are promising for applications in cancer theranostics.